MONGE, C.; GÓMEZ, P. (Eds.) (2018). Innovando la docencia desde la formación del profesorado. Propuestas y realidades. Madrid: Síntesis, 338 páginas, ISBN 978-84-9171-098-1. - Raquel Herrero Marcos (Universidad de La Rioja, 2019)
MONGE, C.; GÓMEZ, P. (Eds.) (2018). Innovando la docencia desde la formación del profesorado. Propuestas y realidades. Madrid: Síntesis, 338 páginas, ISBN 978-84-9171-098-1.